Guidance needs and their relationship to protest behavior and self-harm among homeless and homeles (Journal of the College of Basic Education, 2022)
The current research aims to identify the indicative needs of the research sample, to identify the significance of the differences between the sex variable (males and females) according to the indicative needs scale, to identify the level of protest behavior of the research sample, and to identify the significance of the differences between the sex variable (males and females) according to the scale Protest behavior, identifying the level of self-harm in the research sample, and identifying the significance of the differences between the sex variable (males and females) according to the scale of self-harm and knowing the nature of the relationship and direction between the indicative needs, protest behavior and self-harm in the research sample, and the current research is limited to the homeless and homeless in shelters Affiliated to the Ministry of Labor and Social Affairs in the city of Baghdad for the year (2020-2021), and for the purpose of achieving the research objectives, the researcher built the three measures (indicative needs, protest behavior, and self-harm) to fit the research sample, and the sample was chosen in a random way of (50) homeless and homeless By (25) homeless and (25) homeless, and after analyzing the results, the research reached the following results: That the members of the current research sample have guidance needs, and that males have equal Z of the indicative needs is greater than that of females, and that the members of the current research sample have protest behavior, that males have a greater level of protest behavior than females, and that the members of the current research sample have a high level of self-harm, and that females have a greater level of self-harm than males, It was found that the variable (protest behavior) had the largest contributions, as it came in the first place. As for the variable (self-harm), the results showed that it contributes to counseling needs (second place), and that the two variables contribute to (12.5%) of the total variance in the needs variable. Indicative, and the research came out with a set of recommendations